The origin of food commodities: imports and domestic production in Italy - Zuppiroli, Marco (Progress in Nutrition, 2015)
The theme of “origin of the product” is likely a media and commercial exploitation if not thorough providing the consumer with adequate information. In a few cases he knows some facts which can not be ignored. To this end, the paper aims to provide an updated assessment of the degree of self-sufficiency for the Italian agricultural and food products. To correctly understand the situation, it should be stressed that our country does not have and couldn’t have the potential to provide all the agricultural feedstock needed to carry out, in quantity and quality, all the Italian domestic consumption. Italy is self-sufficient only for a few food consumption, for the rest our country needs to import many raw materials and then export them in the form of finished products, thanks to the capacity and know-how of its processing industry. It is better to endure a trade deficit for raw materials, but to succeed, with the imports, to preserve the industrial potential that ensures value added and income.